Subretinal delivery of erythropoietin alleviates the N-methyl-N-nitrosourea-induced photoreceptor degeneration and visual functional impairments: an in vivo and ex vivo study - Ye Tao; Yue Wang; Zhao Ma; Liqiang Wang; Limin Qin; Lu Wang; Yi Fei Huang; Shizhong Zhang (Taylor & Francis Group, 2017)
Retinitis pigmentosa (RP) is a heterogeneous group hereditary retinal disease that is characterized by photoreceptor degeneration. The present study sought to explore the therapeutic effects of erythropoietin (EPO) on the N-methyl-N-nitrosourea (MNU)-induced photoreceptor degeneration. The MNU-administered mouse or normal control received a subretinal injection of EPO (at the dose of 10U). Twenty-four hours after EPO injection, the retinal EPO levels of experimental animals were quantified. Subsequently, the experimental animals were subjected to optokinetic tests, ERG examination, SD-OCT examination, histology assessment, and immunohistochemistry evaluation. The retinal superoxide dismutase (SOD) activity, malondialdehyde (MDA) content, and expression levels of several apoptotic factors were also quantified. The subretinal injection of EPO up-regulated the retinal EPO level in the retinas of MNU-administered mice. The optokinetic tests and ERG examination suggested the visual functional impairments in MNU-administered mice were ameliorated after EPO treatment. The SD-OCT and histological examination suggested the morphological devastations in MNU-administered mice were alleviated after EPO treatment. The cone photoreceptors in MNU-administered mice were protected from the MNU-induced detrimental effects. Moreover, the EPO treatment rectified the apoptotic abnormalities in MNU-administered mice, and enhanced the expression level of Foxo3, a critical mediator of autophagy. The EPO treatment also mitigated the MDA concentration and enhanced the retinal SOD activity, thereby counteracting the retinal oxidative stress in MNU administered mice. In ophthalmological practice, the subretinal delivery of EPO is a feasible therapeutic strategy to alleviate photoreceptor degeneration. These findings would enrich our pharmacological knowledge about EPO and shed light on the development of an effective therapy against RP.